Facebook satisfaction, life satisfaction: Malaysian undergraduate experience - Hamedi M. Adnan; Samira Rahimi Mavi (Pusat Pengajian Media dan Komunikasi, Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2015)
The central aim of this study was to investigate an approach whereby students’ online social networking produces positive psychological outcomes. Basically, Facebook is a social site that is open to all and closely integrated into the daily experience of most undergraduate students in Malaysia. This study conducted to analyse the association between the number of Facebook friends and the amount of time spent on Facebook with life satisfaction. The purpose of the current study was to investigate what gratifications Malaysian students obtain from Facebook uses. The present study also probed to find out whether gratification obtaining from Facebook uses predicts life satisfaction. In doing so, the theory of the uses and gratification and the theory of the life satisfaction were adopted as theoretical frame work. Our findings of 798 participants, conducting a factor analysis, explored respectively the following gratifications behind Facebook uses: entertainment, communication, social investigation social attention, shared identity and information seeking. Furthermore, using the regression equation, this study failed to find direct association between number of Facebook friends and amount of time using with life satisfaction. The number of Facebook friends while controlling by Facebook motivations could predict life satisfaction. So, it is propounded the view that general uses of social networking sites don’t meet the psychological effects, but the type of certain interaction is the matter. Finally, the findings of this study detected shared identity and social attention as two obtaining gratification that predicted students’ life satisfaction.